Impairment of Ceramide-Mediated Endothelial Instant Membrane Resealing During Diabetes Mellitus - Chen, Yang; Li, Guangbi; Bhat, Owais M.; Li, Xiang; Zhang, Yang; Li, Pin-Lan (Frontiers in Physiology, 2022)
Recent studies have indicated that instant cell membrane resealing (ICMR) controls the activation of NOD-like receptor pyrin domain containing 3 (Nlrp3) inflammasomes in endothelial cells, thereby initiating and promoting vascular inflammation. It remains unknown whether this impaired ICMR occurs under diabetic condition or hyperglycemia contributing to endothelial dysfunction leading to vascular inflammation, a hallmark of diabetic vascular injury. The present study aims to examine whether ICMR occurs during in control and diabetic mice and to explore related molecular mechanisms associated with acid sphingomyelinase (ASM)-mediated ceramide production. Using confocal microscopy, we demonstrated that mouse aortic endothelial cells (MAECs) exposed to high glucose levels exhibited much more retarded ICMR after laser-induced membrane injury, compared to that in control cells. The high glucose-induced impairment of membrane resealing in MAECs was prevented when these cells were pretreated with sphingomyelin or C24-ceramide. Mechanistically, high glucose treatment decreased association of membrane ceramide with annexin A5, an essential element of membrane repair machinery. Consistently, the association of ceramide with annexin A5 was significantly reduced in the coronary arterial endothelium of mice with streptozotocin-induced diabetes mellitus compared to that in non-diabetic control mice. Moreover, a marked reduction of the association of ceramide with annexin A5 was observed in coronary arterial endothelium of ASM knockout mice regardless of their diabetic status. Lastly, high glucose treatment or ASM gene deletion substantially impaired ICMR in coronary arterial endothelium of mice receiving membrane puncturing agents. Collectively, our data suggest that ceramide-mediated ICMR in vascular endothelial cells is impaired during diabetes mellitus due to dissociation of ceramide with annexin A5 and ASM play a critical role in this ICMR.